AN INVESTIGATION OF THE USE OF COHESIVE DEVICES IN STUDENTS' DISCUSSION TEXTS - Ningsih, Putri Rahayu (2016)
the cohesion of the texts, i.e. keeping track of the participants in the text, avoiding redundancy, organizing the ideas into logical order, and connecting parts of the texts to the topic of the text. Based on the findings, it can be concluded that cohesive devices are important devices to create cohesive texts. Teachers are suggested to integrate activities or exercises related to cohesion in the process of teaching writing to help the students to use cohesive devices appropriately to create a cohesive text.